Coupling coordination analysis of agricultural carbon reduction, pollution abatement, green expansion, and growth in Jiangsu Province, China - Zhixian Sun; Yixuan Lu; Xinyue Zheng; Zhiheng Huang; Guanxin Yao (Journal of Agriculture and Food Research, 2025)
Synergistic advancements in agricultural carbon reduction, pollution abatement, green expansion, and growth (ACPGG) are essential for ensuring sustainable agricultural transformation. Focusing on county-level agricultural systems in Jiangsu Province (in a narrow sense), the complex interactions among ACPGG subsystems were elucidated, and a corresponding evaluation index system was established with statistical data and remote sensing data. Using the modified coupling coordination degree (CCD) model, coupling coordination of ACPGG subsystems from 2006 to 2022 was assessed. Spatiotemporal dynamics were analyzed through Dagum Gini coefficient decomposition, standard deviation ellipse, and Markov chain analysis methods complemented by the panel Tobit model to identify factors influencing the CCD. The results revealed that (1) the CCD levels of all four ACPGG subsystems generally increased, but notable interregional imbalance occurred. (2) The provincial average CCD greatly increased, with an 11.37 % increase in 2022 compared with that in 2006. The CCD spatial pattern revealed higher values in the north and lower values in the south, with the level in less than 35 % of counties surpassing intermediate coordination. (3) Interregional differences constituted the main source of overall CCD differences. Across the province, the CCD difference along the northwest‒southeast direction slightly increased. Neighboring counties with higher CCD levels could obtain positive spatial spillover effects. (4) Although there was regional heterogeneity in the CCD-induced driving effect, factors such as the annual average temperature, agricultural mechanization intensity, innovation capacity, and agglomeration yielded significant impacts. These findings provide valuable insights for decision-makers to promote coordinated ACPGG development in key food-producing areas.